Low-Profile Dual-Band and Wideband Optical Mantle Cloaks With Electric and Magnetic Polarizabilities and High Scattering Efficiency - Keyhan Hosseini; Hemn Younesiraad; Alessio Monti; Alessandro Toscano; Filiberto Bilotti (IEEE Access)
A theoretical framework is developed to propose single- and dual-band mantle cloaks composed of low-profile single-layer electrically and magnetically polarizable (EMP) metasurfaces. The target is a dielectric cylinder with a circular cross-section. The metasurface immitances are modeled by Lorentzian functions to model the near-resonance behavior of realistic unit cells. For small targets, to suppress the dominant zeroth-order scattered harmonic, closed-form and semi-closed-form relations are derived for Lorentzian parameters to achieve dual-band and single-band operations, respectively. Compared to pure electric cloaks, the scattering efficiency (SE) for the single-band electric-magnetic cloak experiences a 12 dB improvement, and the cloaking bandwidth is nearly doubled at 350 THz. For larger targets with two significant scattered modes, a semi-analytical approach is developed. Accordingly, compared to a double-layer electric cloak of the same thickness, an improvement of about 7.5 dB in SE and a fivefold bandwidth enhancement at 500 THz are achieved. The proposed modal solution is verified by the method of moments (MoM). EMP metasurfaces mimic the behavior of dielectric metasurfaces, which are necessary for THz and optical bands due to their low loss.